Protein-specific localization of a rhodamine-based calcium-sensor in living cells - Best, Marcel; Porth, Isabel; Hauke, Sebastian; Braun, Felix; Herten, Dirk-Peter; Wombacher, Richard (Organic & biomolecular chemistry, 2016)
A small synthetic calcium sensor that can be site-specifically coupled to proteins in living cells by utilizing the bio-orthogonal HaloTag labeling strategy is presented. We synthesized an iodo-derivatized BAPTA chelator with a tetramethyl rhodamine fluorophore that allows further modification by Sonogashira cross-coupling. The presented calcium sensitive dye shows a 200-fold increase in fluorescence upon calcium binding. The derivatization with an aliphatic linker bearing a terminal haloalkane-function by Sonogashira cross-coupling allows the localization of the calcium sensor to Halo fusion proteins which we successfully demonstrate in in vitro and in vivo experiments. The herein reported highly sensitive tetramethyl rhodamine based calcium indicator, which can be selectively localized to proteins, is a powerful tool to determine changes in calcium levels inside living cells with spatiotemporal resolution.
Gesehen am 11.05.2020